1998
DOI: 10.2108/zsj.15.761
|View full text |Cite
|
Sign up to set email alerts
|

GnRH Analog Stimulates Gonadotropin II Gene Expression in Maturing Sockeye Salmon

Abstract: ABSTRACT-Our previous study suggested that, in the pituitaries of pre-spawning chum salmon, salmon gonadotropin-releasing hormone (sGnRH) stimulates expression of genes for gonadotropin (GTH) IIβ but not for Iβ, since the levels of mRNAs encoding sGnRH and GTH II but not I were increased during the final stages of spawning migration. In the present study, a capsule of GnRH analog (GnRHa) was implanted into the dorsal muscle of maturing sockeye salmon to clarify function of GnRH on expression of GTH subunit gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…In Sockeye Salmon, GnRH stimulated lhb expression while had no effects on fshb (Kitahashi et al, 1998). In goldfish, GnRH stimulated both fshb and lhb gene expression in vivo and in vitro (no matter pituitary fragments or dispersed cells) (Klausen et al, 2001).…”
Section: Reduced Sensitivity Of Gh-transgenic Pituitaries To Stimulatmentioning
confidence: 94%
See 1 more Smart Citation
“…In Sockeye Salmon, GnRH stimulated lhb expression while had no effects on fshb (Kitahashi et al, 1998). In goldfish, GnRH stimulated both fshb and lhb gene expression in vivo and in vitro (no matter pituitary fragments or dispersed cells) (Klausen et al, 2001).…”
Section: Reduced Sensitivity Of Gh-transgenic Pituitaries To Stimulatmentioning
confidence: 94%
“…However in catfish, GnRH inhibited lhb expression at 2 h, 4 h after GnRH injection and stimulated lhb expression at 8 h after GnRH injection in vivo while only inhibited lhb expression in vitro (Rebers et al, 2002). In vivo treatment of salmon with GnRH using fish from different developmental stages results in different lhb expression pattern (Dickey and Swanson, 2000;Kitahashi et al, 1998). These differing results indicate that gonadotroph responsiveness to GnRH is dependent on experiment conditions (in vivo or in vitro) and developmental stages.…”
Section: Reduced Sensitivity Of Gh-transgenic Pituitaries To Stimulatmentioning
confidence: 96%
“…sGnRH facilitated electric activity of central neurosecretory cells (NSCs) (Saito et al, 2003). GnRHa increased amounts of mRNAs encoding gonadotropin (GTH) II (Kitahashi et al, 1998a) and SL (Taniyama et al, 2000;Bhandari et al, 2003) in the pituitary, and further accelerated final maturation (Fukaya et al, 1998). These lines of evidence suggest that sGnRH neurons are activated during upstream migration, and coordinately regulate migratory behavior and final gonadal maturation.…”
Section: Introductionmentioning
confidence: 95%
“…Expression of GTH subunit genes in the pituitary gland was examined and revealed that the levels of GTHa and LHb mRNAs in GnRHa-implanted fish were higher than those in control fish, but the levels of FSHb mRNA showed no change (Kitahashi et al 1998b). Implantation of GnRHa caused a significant elevation of serum DHP levels in both sexes, but had no effect on levels Changes in serum steroid hormone levels of male and female chum salmon during homing migration from Site G to Site A (Fig.…”
Section: -4 Homing Profiles Of Sockeye Salmon By Hormone and Antagomentioning
confidence: 96%